2014
DOI: 10.1186/1472-6882-14-234
|View full text |Cite
|
Sign up to set email alerts
|

An ethyl acetate fraction derived from Houttuynia cordata extract inhibits the production of inflammatory markers by suppressing NF-кB and MAPK activation in lipopolysaccharide-stimulated RAW 264.7 macrophages

Abstract: BackgroundHouttuynia cordata Thunb. (Saururaceae) has been used in traditional medicine for treatment of inflammatory diseases. This study evaluated the anti-inflammatory effects of an ethyl acetate fraction derived from a Houttuynia cordata extract (HCE-EA) on the production of inflammatory mediators and the activation of nuclear factor-κB (NF-κB) and mitogen-activated protein kinases (MAPKs) in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages.MethodsTo measure the effects of HCE-EA on pro-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Similar to water extracts, ethyl acetate fraction of HC was also shown to suppress nuclear translocation of NF-κB p65 subunit and attenuated the activation of MAPKs (p38 and JNK) in LPS primed RAW 264.7 cells. Furthermore, the extract showed to significantly reduce the NO, PGE2, TNF-α and IL-6 levels (Chun et al, 2014).…”
Section: Potential Role Of H Cordata Against Inflammationmentioning
confidence: 90%
“…Similar to water extracts, ethyl acetate fraction of HC was also shown to suppress nuclear translocation of NF-κB p65 subunit and attenuated the activation of MAPKs (p38 and JNK) in LPS primed RAW 264.7 cells. Furthermore, the extract showed to significantly reduce the NO, PGE2, TNF-α and IL-6 levels (Chun et al, 2014).…”
Section: Potential Role Of H Cordata Against Inflammationmentioning
confidence: 90%
“…MAPK, an intracellular serine/threonine protein kinase, is an important signaling system for cell-mediated extracellular signals to intracellular responses, and plays a key role in cell proliferation, apoptosis, in ammation, immunity and angiogenesis [22]. Studies have found that inhibiting MAPK signaling pathway activation can reduce the occurrence of in ammatory response [23]. So, this research postulated that MAPK might play an important regulatory role in the occurrence and development of vasculitis in Kawasaki disease.…”
Section: Discussionmentioning
confidence: 93%
“…However, the present study demonstrated through western blot analysis and immunofluorescence staining that the translocation of NF-κB was attenuated by lovastatin in LPS-stimulated RAW264.7 cells. Previously, studies have shown that NF-κB participates in the expression of iNOS and TNF-α (33)(34)(35). IκBα binds to NF-κB and suppresses its translocation; when IκBα is phosphorylated and degraded by proteasomes, NF-κB is activated and translocates into the nucleus (36).…”
Section: Discussionmentioning
confidence: 99%